Micro-Level Affect Dynamics in Psychopathology Viewed From Complex Dynamical System Theory. (October 2015) - Wichers, M.; Wigman, J. T. W.; Myin-Germeys, I.
This article discusses the role of moment-to-moment affect dynamics in mental disorder and aims to integrate recent literature on this topic in the context of complex dynamical system theory. First, we will review the relevance of temporal and contextual aspects of affect dynamics in relation to psychopathology. Related to this, we will discuss recent insights resulting from a network view on affect dynamics in psychopathology. Next, we explore how we can reconcile literature findings from a perspective of complex dynamical system theory. Finally, future directions with regard to personalized assessment of risk and diagnostic use are discussed.